Analysis of the Factors Affecting Lumbar Segmental Lordosis After Lateral Lumbar Interbody Fusion. Issue 14 (15th July 2020) - Otsuki, Bungo; Fujibayashi, Shunsuke; Takemoto, Mitsuru; Kimura, Hiroaki; Shimizu, Takayoshi; Murata, Koichi; Matsuda, Shuichi
Abstract : Study Design: Retrospective study. Objective: To elucidate factors that determine segmental lordosis after lateral retroperitoneal lumbar interbody fusion (LLIF) with percutaneous pedicle screw fixation. Summary of Background Data: LLIF has been widely used in degenerative lumbar spine surgery. However, the detailed mechanisms that determine segmental lordosis are still unknown. Methods: A total of 69 patients who underwent LLIF with posterior pedicle screw fixation without posterior osteotomy were analyzed. Computed tomography was performed before and within 2 weeks after surgery, and segmental lordotic angle (SLA) after surgery (Post-SLA) was predicted using multiple regression analysis. Explanatory factors considered in this study included SLA before surgery (Pre-SLA), disc height before surgery (DiscH), cage position (CageP; distance between the center of the cage and the center of the disc, where a positive value indicates an anterior cage position), cage angle (CageA), cage height (CageH), CageH–DiscH (amount of lift up), previous decompression surgery, and level fused. Results: A total of 102 levels were analyzed. Multiple regression analysis revealed that the Post-SLA can be predicted with three independent variables, CageP, Pre-SLA, and CageH–DiscH and the adjusted R 2 was 0.70. In cases when the cage was located anteriorly (CageP > 3 mm), Post-SLA was greater with larger CageH, larger CageA, and larger Pre-SLA. When the cage was located in the middle (3 mm ⩽CageP ⩽–1 mm), Post-SLA was greater with larger CageP, larger Pre-SLA, and without previous decompression surgery. If the cage was located posteriorly (CageP < –1 mm), Post-SLA was greater with smaller CageH–DiscH and greater Pre-SLA. Conclusion: To gain maximum segmental lordosis in LLIF, the cage should be located anteriorly. Furthermore, if the cage can be located anteriorly, a thicker cage with proper angle cage will gain segmental lordosis. If the cage is located posteriorly, a thin cage should be selected. Level of Evidence: 3 Abstract : Factors affecting postoperative segmental lordosis after lateral lumbar interbody fusion with percutaneous pedicle screw fixation were analyzed at 102 disc levels. To gain maximum segmental lordosis, a thick cage should be located anteriorly to the disc space. If the cage is forced to be located posteriorly, a thin cage should be selected.